Posttranslational Modifications in Conserved Transcription Factors: A Survey of the TALE-Homeodomain Superclass in Human and Mouse - Reichlmeir, Marina; Elias, Lena; Schulte, Dorothea (Frontiers in Cell and Developmental Biology, 2021)
Transcription factors (TFs) guide effector proteins like chromatin-modifying or -remodeling enzymes to distinct sites in the genome and thereby fulfill important early steps in translating the genome’s sequence information into the production of proteins or functional RNAs. TFs of the same family are often highly conserved in evolution, raising the question of how proteins with seemingly similar structure and DNA-binding properties can exert physiologically distinct functions or respond to context-specific extracellular cues. A good example is the TALE superclass of homeodomain-containing proteins. All TALE-homeodomain proteins share a characteristic, 63-amino acid long homeodomain and bind to similar sequence motifs. Yet, they frequently fulfill non-redundant functions even in domains of co-expression and are subject to regulation by different signaling pathways. Here we provide an overview of posttranslational modifications that are associated with TALE-homeodomain proteins and discuss their likely importance for the biology of these TFs.